Un modèle de projection des prix utilisant les relations intersectorielles de l’économie canadienne - Rioux, R. (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
This paper describes a simple cost-push price model which has been developed at the Structural Analysis Division of Statistics Canada.This price model is a traditional input/output cost-push model which has been adapted to utilize the rectangular industry by commodity input/output tables for Canada. It can be considered as the "dual" of the output model. Instead of analysing the propagation of demand through the economic system, the price model serves to analyse the propagation of factor prices throughout the system.The purpose of such a price formation model is to determine the impact on industry selling prices and domestic commodity prices arising from a change in impart commodity prices and primary input prices.This price model is of a static type; it accepts no substitutions and its structure is quite rigid. It is considered as being an annual model although it can be used for a different time period.This model is fully operational and is widely used by many government and private agencies.